Corrosion behavior of Monofrax K‐3 refractory in borosilicate‐based model low activity waste glass melts. Issue 6 (13th February 2023) - Xu, Xinyi; Saini, Rajan; Koray Akdoğan, Enver; McCloy, John Stuart; Goel, Ashutosh
Abstract: Owing to its good chemical and thermal durabilities at high temperatures, Monofrax K‐3 refractory is widely used in nuclear waste vitrification as a lining material in melting vessels. However, the corrosion of K‐3 refractory during the vitrification of nuclear waste is a serious problem because it affects the melter's safety, performance, and lifetime. Therefore, in the present study, we have focused on unearthing the impact of glass network formers, such as SiO2, B2 O3, and Al2 O3, in a model nuclear waste glass composition on the corrosion of Monofrax K‐3 refractory. The corrosion tests have been performed per ASTM C621 at 1150°C for 5 days. The dimensional measurements on corroded K‐3 refractory suggest that Al2 O3 and SiO2 tend to reduce the refractory corrosion (neck loss), with the effect of Al2 O3 being significant. A corroded region on the K‐3 refractory at the melt–refractory interface is observed. The corrosion occurs via a coupling of the melt infiltration induced by a capillary effect and the dissolution of Al, Mg, and Fe components from K‐3 into the melt through chemical reactions. A Cr‐rich layer is retained on the glass contact surface of the corroded K‐3 refractory.